Osteology and systematics of Uberabatitan ribeiroi (dinosauria; sauropoda): a late cretaceous titanosaur from Minas Gerais, Brazil - Silva Junior, Julian Cristian Gonçalves da (2018)
Uberabatitan ribeiroi is a Late Cretaceous titanosaur (Dinosauria, Sauropoda) from Brazil. Here we provide a detailed revision of all its available specimens, including new elements from the type-locality, helping to increase the anatomical knowledge of the taxon. Two new autapomorphies are proposed: (1) line through the distal condyles of the femur is perpendicular to the long axis of the shaft in anterior view and (2) astragalus with a well-developed anteroposteriorlly crest that delimits distally the tibial articulation. Further, linear regressions were conducted in an attempt do circumscribe specimens within the type-series, revealing that this is composed of several individuals, with sizes varying from 7 to 26 meters. Finally, phylogenetic analyses including U. ribeiroi show that the Brazilian taxon corresponds to a non-Saltasauridae titanosaur.